Sex reversal mechanism in Nile tilapia Oreochromis niloticus (Linnaeus, 1758) by manipulation of aromatase gene expression - Upmal Deswira; Agus Oman Sudrajat; Dinar Tri Soelistyowati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
Sex reversal is a sex conversion technique to be male or female. This research was conducted to evaluate the mechanism of sex reversal in tilapia on the use of aromatase inhibitors (AI), honey and pesticide. The eye spot embryo of Nile tilapia was immersed into those solutions and examined the expression of aromatase gene and sex ratio. The sex reversal was carried out by immersion of eye spot embryo for 24 hours using 20 mg L-1 AI (imidazole), 10 ml L-1 honey (Perhutani, longan flower), and 1 ^L L-1 pesticide (Decis: deltamethrin 25 g L-1). Aromatase gene expression was analyzed on 1st and 8th day after treatment. Larvae were reared until 75 days-old. The level of gene expression of ovarian type aromatase in imidazole, honey, and pesticide treatment on 1st day after treatment were lower than control. While, on 8th day the lowest level of gene expression was on imidazole treatment and the highest was on pesticide treatment. The results indicated that masculinization occurred in imidazole treatment and feminization occurred in pesticide treatment which showed by male percentage that significantly different from the control (p<0.05). The male percentage of control, imidazole, honey, and pesticide were 68.32%, 80.77%, 70.93% and 50.45%, respectively. Honey treatment was not significantly different from control. In conclusion, sex reversal was influenced by modulation of gene expression of ovarian type aromatase, the increasing of gene expression of ovarian type aromatase caused feminization, and otherwise the decreasing of gene expression caused masculinization in early development stage of nile tilapia. Abstrak Alih kelamin merupakan suatu teknik pengalihan kelamin menjadi jantan atau betina. Penelitian ini bertujuan mengeva-luasi mekanisme alih kelamin ikan nila pada penggunaan penghambat aromatase, madu, dan pestisida. Ikan nila fase bintik mata direndam dalam tiga larutan tersebut dan diamati ekspresi gen aromatase dan nisbah kelaminnya. Peren-daman dilakukan selama 24 jam menggunakan penghambat aromatase (imidazole) 20 mg L-1, madu (Perhutani, bunga kelengkeng) 10 ml L-1, dan pestisida (Decis: deltametrin 25 g L